Diaspora and Syncretism: Marriage Rites in Yorùbá Homeland and Abroad - Olanike Lawore (Yoruba Studies Review)
The marriage institution is as old as the human race and is valued for companionship and procreation. The Yorùbá race accords great importance to this institution and has a distinctive manner of contracting its nuptials which underscores the sacredness it attaches to marriage. The importance attached to this union is evident in parents’ preparation even before the girl-child is born, including contracting a marriage proposal on her behalf. This marks the beginning of a long process that will eventually culminate in future marriage. As Yorùbá people are found all over the globe, the marital rites are transferred from the original soil to the diaspora, the result of which is the syncretic practices that are associated with marital practices abroad. This essay therefore engages in a comparative exercise, identifying marital rites in the diaspora that have maintained close ties with homeland and those that have diverged from them.